Does Standing Affect Acetabular Component Inclination and Version After THA? - Polkowski, Gregory G. (Springer-Verlag, 2012)
BACKGROUND: Avoiding complications after hip arthroplasty with hard-on-hard bearings, especially metal-on-metal, correlates with the position of the acetabular component. Supine imaging with conventional radiography has traditionally been utilized to assess component inclination (abduction), as well as anteversion, after THA and surface replacement arthroplasty (SRA). However, most adverse events with hard bearings (excessive wear and squeaking) have occurred with loading. Standing imaging, therefore, should provide more appropriate measurements. QUESTIONS/PURPOSES: We determined whether standing changed standard measurements of acetabular component position using a novel biplanar imaging system compared to traditional supine imaging. METHODS: We performed simultaneous biplanar standing imaging of the lower extremity with a novel imaging system using low radiation collimated beam on 46 patients who underwent THA (23) or SRA (23). Patients who had previously undergone THA had standard CT scans performed. For patients who underwent SRA, we compared acetabular inclination in the supine versus double-limb and single-limb standing. RESULTS: Standing anteversion differed from supine anteversion by greater than 5° for 12 of 23 patients who underwent THA (range, 5°–16°). For patients who underwent SRA, 13 of 23 patients exhibited a difference of greater than 3° in inclination between supine and double-limb standing images, and six of 23 patients exhibited a difference of greater than 3° in inclination between supine and single-limb standing images. CONCLUSIONS: Standing changed the acetabular inclination and version in a substantial percentage of patients undergoing hip arthroplasty.